Ubushakashatsi mu Bumenyi Nyamuntu n'Imibanire y'Abantu - Mukama, Evode; Nkusi, Laurent (African Minds, 2019)
Research in developed countries is often considered as a means to pave the way towards sustainable development in different areas of the society including science and technology, the economy, governance and security. Researchers in developing countries rarely have the opportunity to use their indigenous languages to design, plan and conduct research. Nor do they communicate in their indigenous languages to share their insights and learnings from other parts of the world with colleagues or students. Utilising the languages that researchers, students and teachers, policymakers, the community, and others interested in research understand better can help to generate new knowledge embedded in local realities where sustainable development needs to take root. That is why this book is in Kinyarwanda. The authors hope that writing this book in Kinyarwanda will increase research capacity in the humanities and social sciences in Rwanda and in the region. And that it will increase interaction between all key stakeholders in the planning and conducting of research as well as in analysing, monitoring and evaluating the research process and its outputs.]